Hypodense liver lesions in patients with hepatic steatosis: do we profit from dual-energy computed tomography? - Nattenmüller, Johanna; Hosch, Waldemar; Nguyen, Tri-Thien; Skornitzke, Stephan; Jöres, Andreas; Grenacher, Lars; Kauczor, Hans-Ulrich; Sommer, Christof; Stiller, Wolfram; Sommer, Christof M (European Radiology, 2015)
Purpose: To evaluate dual-energy CT (DECT) imaging of hypodense liver lesions in patients with hepatic steatosis, having a high incidence in the general population and among cancer patients receiving chemotherapy.Methods: One hundred and five patients with hepatic steatosis (liver parenchyma <40 HU) underwent contrast-enhanced DECT with reconstruction of pure iodine (PI), optimum contrast (OC), 80 kVp, and 120 kVp-equivalent data sets. Image noise (IN), lesion to liver signal to noise (SNR) and contrast to noise (CNR) ratios were quantitatively analysed; image quality was rated on a 5-point scale (1, excellent; 2, good; 3, fair; 4, poor; 5, non-diagnostic) by two independent reviewers.Results: In 21 patients with hypodense liver lesions, IN was lowest in PI followed by 120 kVp-equivalent and OC, and highest in 80 kVp. SNR was highest in PI (1.30), followed by 120 kVp-equivalent (0.72) and 80 kVp (0.63), and lowest in OC (0.55). CNR was highest in 120 kVp-equivalent (4.95), followed by OC (4.55) and 80 kVp (4.14), and lowest in PI (3.63). The 120 kVp-equivalent series exhibited best overall qualitative image score (1.88), followed by OC (1.98), 80 kVp (3.00) and PI (3.67).Conclusion: In our study, the 120 kVp-equivalent series was best suited for visualization of hypodense lesions within steatotic liver parenchyma, while using DECT currently seems to offer no additional diagnostic advantage.Key Points: • Hepatic steatosis has high incidence in the general population and following chemotherapy. • Hypodense liver lesions can be obscured by steatotic liver parenchyma in CT. • Low kV p -CT shows no advantage in detecting hypodense lesions in steatotic livers. • Additional DECT image information does not improve visualization of hypodense lesions in steatosis. • 120 kV p -equivalent imaging yields best quantitative and qualitative image analysis results.